(untitled) (Research, Society and Development, 2019)
The present theoretical study seeks to understand the practice of research through the concept of the event proposed by the Philosophy of Difference of Gilles Deleuze, with the intention of reflecting on the possible contributions that this concept can bring to the contemporary ways of researching. It is indicated, from the theory of Philosophies of Difference, an emphasis on the concept of difference and its relationship with a form of research that emphasizes the learning process that happens in the research. It is a form of research that does not simply focus on results and final objectives, but which gives meaning and value to what actually happens during the research process itself. Through the concept of event, one can highlight learning and the infinite constructions and creations that take place during research - learning is what makes sense and value in this way of researching.